2021
DOI: 10.3390/jcm10092035
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Microscopy in Neurosurgery: State of the Art of Actual Clinical Applications

Abstract: Achievement of complete resections is of utmost importance in brain tumor surgery, due to the established correlation among extent of resection and postoperative survival. Various tools have recently been included in current clinical practice aiming to more complete resections, such as neuronavigation and fluorescent-aided techniques, histopathological analysis still remains the gold-standard for diagnosis, with frozen section as the most used, rapid and precise intraoperative histopathological method that per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…It provides noninvasive real-time imaging. However, this technique is limited by the need for potential toxic fluorophores for contrast-enhancement and microstructure visualization [25]. Moreover, this technique requires intense user training and merely provides non-static gray scale confocal microscopic images [26][27][28], which is challenging imaging data to interpret even for trained neuropathologists.…”
Section: Discussionmentioning
confidence: 99%
“…It provides noninvasive real-time imaging. However, this technique is limited by the need for potential toxic fluorophores for contrast-enhancement and microstructure visualization [25]. Moreover, this technique requires intense user training and merely provides non-static gray scale confocal microscopic images [26][27][28], which is challenging imaging data to interpret even for trained neuropathologists.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the lack of a reference catalogue has been mentioned. Particularly in the beginning, the interpretation of images can be challenging or imprecise, including the risk for misdiagnosis [12]. However, this is most likely only a temporary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown in several studies, both for in vivo and ex vivo analyses of animal and human brain tumor tissue [1,[8][9][10][11]. The authors of a recent systematic literature review, however, found the evidence-base to be insufficient to formulate a definite conclusion on the usefulness of CLE for intraoperative decision support [12]. Yet, several other medical fields such as gastroenterology [13,14], urology [15], and others [5,16,17] report promising results for the effective and safe use of CLE.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of using these methods is to detect tumor cells infiltration of brain tissue; also, they can be thought of as methods of OCT-based target biopsy during stereotactic procedures. The results of the current investigation show the perspectives of using confocal microscopy [98][99][100], Raman spectroscopy [101][102][103], fluorescence lifetime spectroscopy and imaging [104][105][106][107] and OCT [20,24,108]. Providing high-resolution imaging optical technologies may be regarded as substitution or, more likely, supplementation of traditional imaging such as MRI, ultrasound (US), 5-ALA or other fluorescence agents [96,97,109].…”
Section: The Place Of Oct Among Other Intraoperative Imaging Techniquesmentioning
confidence: 99%